1991
DOI: 10.1099/00221287-137-9-2163
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chitinase synthesis in Trichoderma harzianum

Abstract: The production of chitinase by Trichoderma species is of interest in relation to their use in biocontrol and as a source of mycolytic enzymes. Fourteen isolates of the genus were screened to identify the most effective producer of chitinase. The best strain for chitinase was Trichoderma hurziunum 39.1, and this was selected for study of the regulation of enzyme synthesis. Washed mycelium of T. hurziunum 39.1 was incubated with a range of carbon sources. Chitinase synthesis was induced on chitin-containing medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 28 publications
7
44
2
Order By: Relevance
“…In present investigation, it was found that chitinase and b-1,3-glucanase enzyme activities was increased with the substitution of specific carbon source at 1% concentration. These findings is in accordance with Ulhoa and Peberdy [25] where they suggested that chitinase activity was substrate's concentration dependent above 0.5% (w/v) chitin there was no further synthesis of chitinase in the growth medium by T. harzianum was increased up to 1% concentration, whereas b-1,3-glucanase enzyme production was increase up to 1% concentration of laminarin but decreased at higher concentrations. This may be due to the fact that at higher concentration of sugar activity of this enzyme was inhibited.…”
Section: T Viride (Tgd1)supporting
confidence: 91%
See 1 more Smart Citation
“…In present investigation, it was found that chitinase and b-1,3-glucanase enzyme activities was increased with the substitution of specific carbon source at 1% concentration. These findings is in accordance with Ulhoa and Peberdy [25] where they suggested that chitinase activity was substrate's concentration dependent above 0.5% (w/v) chitin there was no further synthesis of chitinase in the growth medium by T. harzianum was increased up to 1% concentration, whereas b-1,3-glucanase enzyme production was increase up to 1% concentration of laminarin but decreased at higher concentrations. This may be due to the fact that at higher concentration of sugar activity of this enzyme was inhibited.…”
Section: T Viride (Tgd1)supporting
confidence: 91%
“…were grown in media supplemented with either autoclaved mycelium or purified host fungal cell walls [7,24]. Ulhoa and Peberdy [25] found that products of chitin degradation also …”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…These conditions have been described as "simulated antagonism" (13,14,30,45). These observations, together with the fact that chitin and ␤-1,3-glucan are the main skeletal polysaccharides of fungal cell walls (except those from Oomycetes, which contain ␤-glucans and cellulose) (3,34), suggest that chitinases and ␤-1,3-glucanases act as the key enzymes in the lysis of phytopathogenic fungal cell walls during the antagonistic action of Trichoderma.…”
mentioning
confidence: 93%
“…This method works on the concentration of N-acetyl glucosamine (NAG), which is released as a result of enzymatic action 22 . The 2mL reaction mixture contained 0.5 mL of 0.5% colloidal chitin in acetate buffer (pH 5.5), 0.5 mL crude enzyme extract and 1mL distilled water.…”
Section: Chitinase Activity Assaymentioning
confidence: 99%